1994
DOI: 10.1002/ajmg.1320500205
|View full text |Cite
|
Sign up to set email alerts
|

Wisconsin Stillbirth Service Program: II. Analysis of diagnoses and diagnostic categories in the first 1,000 referrals

Abstract: The Wisconsin Stillbirth Service Program has provided a mechanism for the collection and analysis of unbiased and representative information concerning stillborn infants. Generated diagnoses and diagnostic categories within the first 1,000 referrals (including 789 stillbirths) is summarized here. Among all referred stillborns, 24.5% were found to have an identifiable intrinsic fetal cause of death. Specific diagnoses were extraordinarily heterogeneous, with about 85 different processes identified with this gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
58
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(59 citation statements)
references
References 26 publications
1
58
0
Order By: Relevance
“…It has been shown that DNA extraction and accurate genotyping was possible on placental tissue of macerated fetuses [Derom et al, 1991]. Maceration should, however, not be regarded as a reason to exclude a genetics consultation [Pauli et al, 1994b]. A genetics consultation was obtained in our study only 12% of the time.…”
Section: Discussionmentioning
confidence: 94%
“…It has been shown that DNA extraction and accurate genotyping was possible on placental tissue of macerated fetuses [Derom et al, 1991]. Maceration should, however, not be regarded as a reason to exclude a genetics consultation [Pauli et al, 1994b]. A genetics consultation was obtained in our study only 12% of the time.…”
Section: Discussionmentioning
confidence: 94%
“…Some type of fetal abnormalities like congenital anomalies, infection, non-immune hydrops, malnutrition etc. account for 25-40% of all stillbirths [6,7]. Pasztor et al, were able to provide exact cause of death in 57.9% cases in their study on identification of causes of still birth through autopsy and placental examination reports.…”
Section: Discussionmentioning
confidence: 99%
“…Cases with multiple congenital malformations were specific to autosomal recessive single gene disorder that have recurrence risk of 25% [9]. Majority of stillbirths attributed to fetal causes in the Winsconsin Stillbirth Service Program had a major structural malformation identified at autopsy [7]. Faye Petersen and colleagues [5] found that one-third of fetal deaths were caused by structural anomalies of which neural tube defects, hydrops and congenital heart disease were the most common.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent paper, Pauli and Reiser [1994] using a population of 1,000 stillborn infants in a pathology study, observed two cases with asplenia and five with polysplenia. These figures support our observation that polysplenia is more frequent than asplenia.…”
Section: Alteration Of Normal Body Asymmetrymentioning
confidence: 96%